A new unified model for channel thermal noise of deep sub-micron RFCMOS - Ong, Shih Ni (2010)
A new unified model for circuit simulation is presented to predict the high frequency channel thermal noise of deep sub-micron MOSFETs in strong inversion region. Based on the new channel thermal noise model, the simulated channel thermal noise spectral densities of the devices fabricated in a 0.13μm RFCMOS technology process are compared to the channel noise directly extracted from RF noise measurements.